Caracterização funcional do gene ypkA, homólogo de ypk1 em levedura, no fungo patógeno oportunista humano Aspergillus fumigatus - Godoy, Naiane Lima (Universidade Federal de São Carlos, 2016)
Aspergillus fumigatus is an opportunistic pathogenic filamentous fungus, and the causative agent of aspergillosis, including the invasive pulmonary aspergillosis in immunocompromised individuals, most lethal form of the disease. As in all eukaryotes, the plasma membrane of A. fumigatus is composed of sterols, glycolipids and sphingolipids. The sphingolipids molecules are structural elements that participate in the regulation of the actin cytoskeleton endocytosis, and cell growth. In Saccharomyces cerevisiae, the sphingolipid synthesis is regulated by proteins such as the "AGC kinases" known as Ypk1p and Ypk2p that inactivate Orm1p and Orm2p, which are inhibitory proteins of the serine palmitoyltransferase (SPT) enzyme, the first enzyme that participates in biosynthetic pathway of sphingolipids. Thus, Ypk1/2p are responsible for stimulating the production of sphingolipids in response to several cellular stress factors, such as cell wall stress and heat stress. Here, we aimed to expand the study of sphingolipid biosynthesis in A. fumigatus by functional characterization of the ypkAYPK1 gene by establishing its role in the regulation of sphingolipid synthesis and in the maintenance of cell integrity. To accomplish this goal, one null mutant strain ΔypkAypk1 and a conditional mutant strain niiA::ypkA of A. fumigatus were obtained. The mutant strains were characterized by phenotypic tests aimed at understanding the role of this gene in sphingolipid synthesis, virulence and pathogenicity of this fungus. Subsequently real time RT-PCR experiments were performed to quantify the expression of this gene in conditions of heat stress. The results indicated that deletion of the gene ypkA promotes changes in the development of the fungus, which presents severe defects in the vegetative growth and absence of conidia. In addition, the conditional mutant shows increased sensitivity to lipid synthesis inhibitory drugs. The results also indicate that there is no interaction between genetic ypkA and pathway genes of the cell wall. Thus, we propose that protein kinase YpkA in A. fumigatus is related to vegetative growth and participates in the sphingolipid biosynthesis in A. fumigatus, contributing to the development and integrity of the fungal cell.
Functional characterization of the ypkA gene, an ypk1 homologous in yeast, on the human opportunist pathogenous fungus Aspergillus fumigatus
Keywords: Esfingolipídios; Aspergillus fumigatus; Sphingolipids; CIENCIAS BIOLOGICAS::GENETICA